IBM USAHA JAMU TRADISIONAL PADA KELOMPOK PKK SEKARPURO KABUPATEN MALANG - Latifah, Sri Wahjuni (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2016)
Implementation of the service was conducted in the village ofSekarpuro Malang. Activity focused on the environment RW9 because has some excellent potential that crops ofvegetables and spices. Each house is required to havevegetables and spices for minimal ten kinds, peppers,tomatoes, cabbage, basil, kale, spinach, mustard greens, beansand eggplant. While these types of spices are grown include:turmeric, saffron and white, kencur, ginger, white ginger, redginger, galangal, lemon grass andothers.The problems faced by partners are: (1)lack of knowledge inthe healthy beverage processing and medicinal herbs, so thatproduct quality standards and the sale price hasn?tcomptetive.(2) Lack of knowledge and skills of members in the field ofmarketing that they are pessimistic to sell to a wider marketProgram execution method of empowerment that carried thepotential members of the group and the potential of the naturalresources of the area environment. Based on the targetaudience who have been in service activities, it can be formedof two businesses that making herbal drinks such as cidertoga, passion fruit syrup and traditional herbal medicinemanufacture that produces fresh herbs and herbal instant. Inthe field of production has developed into six types ofproducts from only two types of products. While in thegeneral field of business licenses has been done so that theproduct is expected to be accepted by the market. In the fieldof marketing has made the introduction of products with avariety of activities and models of traditional marketing is stilldone through leaflets, door to door and exhibits SMEs.Besides, available change over hygienes packaging andlabeling. Administration and finance training activities hashelped entrepreneurs in setting records with good activity, andcan be used to determine accurately the costofproduction.